Novel 5-fluorouracil complexes of Zn(ii) with pyridine-based ligands as potential anticancer agents. Issue 13 (11th March 2022) - Icsel, Ceyda; Yilmaz, Veysel T.; Aygun, Muhittin; Erkisa, Merve; Ulukaya, Engin
Abstract : A Zn(ii ) complex of 5-fluorouracil with bis(2-pyridylmethyl)amine is highly cytotoxic against A549 cells compared to both cisplatin and 5-fluorouracil and induces apoptotic cell death via excessive ROS generation and mitochondrial and DNA damage. Abstract : A series of novel Zn(ii ) complexes of 5-fluorouracilate (5-FU), namely [Zn(5-FU)2 (bpy)] (1 ), [Zn(5-FU)2 (phen)] (2 ), [Zn(5-FU)2 (dpya)]·H2 O (3 ), [Zn(5-FU)2 (bpyma)]·2H2 O (4 ) and [Zn(5-FU)2 (terpy)]·H2 O (5 ), were synthesized and structurally characterized by spectroscopic methods and X-ray crystallography. 5-FU was coordinated to Zn(ii ) via the deprotonated N3 site and also presented the N1 and N3 linkage isomerism in 4 and 5 due to its tautomerism. The antiproliferative activity of the complexes was studied against lung (A549), breast (MDA-MB-231), colon (HCT116) and prostate (DU145) cancer cell lines. Complexes 1, 4 and 5 except 2 and 3 showed potent growth inhibitory activity towards selected cancer cells. Remarkably, 4 was highly cytotoxic towards A549 and MDA-MB-231 cell lines, being more active than the clinical drugs cisplatin and 5-FU. In addition, 4 was not toxic to normal lung cells (BEAS-2B). The complex exhibited a significantly high affinity towards DNA as assessed by gel electrophoresis and DNA docking. The mechanistic studies of 4 in A549 cells indicated that the complex induced apoptotic cell death as evidenced via caspase 3/7 activity, Bcl2 inactivation, annexin V and DAPI/PI staining. 4 further elevated the levels of reactive oxygen species (ROS), depolarized mitochondria and enhanced the expression of γ-H2AX, thus contributing to its remarkable anticancer activity.